The Civil War in cyberspace today - Matilde EIROA (Studia Historica: Historia Contemporánea, 2015)
The appeal of the Spanish Civil War in the online world is a phenomenon deserving of attention, as an event that took place more than 75 years ago which still arouses debate and the curiosity of many. It is surprising that the media world considers it “newsworthy” and that it has an important presence on the Internet — on blogs, websites, You Tube, and even social media platforms such as Facebook and Twitter. This article examines all mention of the Civil War in online media. We start from the idea that the features of the online world allow for an extensive and multifaceted production of media of content which is more cultural, more social, and more attuned to the passing of time.